Neurofibromatosis Type 1 Complicated by Atypical Coarctation of the Thoracic Aorta. (4th March 2013) - Kimura, Masato; Kakizaki, Shuhei; Kawano, Kengo; Sato, Shinichi; Kure, Shigeo
Abstract : Neurofibromatosis type 1 (NF1) is a relatively common autosomal dominant genetic disorder with a prevalence of 1 in 3, 000 (0.03%) at birth. Clinical features are café-au-lait macules, intertriginous freckling, dermal neurofibroma, iris hamartoma (Lisch nodules), and learning disability. NF1 vasculopathy is a serious but underrecognized complication involving the cerebrovascular and cardiovascular systems. The incidence of hypertension in patients with NF1 is around 1% and is associated mainly with renal artery stenosis in children. Only a few cases of thoracic aortic coarctation in association with hypertension and neurofibromatosis have been reported. Here we describe the case of a 4-year-old girl who presented with NF1 and hypertension due to atypical coarctation of the thoracic aorta. The diagnosis of coarctation of the thoracic aorta at the Th5-to-Th6 level was made following catheterization with a pressure gradient of 40 mmHg. The patient underwent surgery comprising resection of the coarctation of the thoracic aorta and graft interposition. On the basis of our findings, annual assessment of blood pressure is advised for patients with NF1.